2022
DOI: 10.7554/elife.78941
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal temperature perception induces specific defenses that enable C. elegans to cope with the enhanced reactivity of hydrogen peroxide at high temperature

Abstract: Hydrogen peroxide is the most common reactive chemical that organisms face on the microbial battlefield. The rate with which hydrogen peroxide damages biomolecules required for life increases with temperature, yet little is known about how organisms cope with this temperature-dependent threat. Here, we show that Caenorhabditis elegans nematodes use temperature information perceived by sensory neurons to cope with the temperature-dependent threat of hydrogen peroxide produced by the pathogenic bacterium Enteroc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 157 publications
0
5
0
Order By: Relevance
“…We observed that only animals expressing ALG-2(CD) in alg-1(null) background were the only ones showing reduced fitness to a level greater than seen in alg-1(null) animals (Figure 1C , S3A ). As an increased growing temperature creates physiological stress ( 48 , 49 ), we next surveyed the phenotypes of the different mutant animals by maintaining them for at least three generations at 25°C. In this specific condition, while single mutants, alg-1 and alg-2 catalytically dead animals displayed no significant health issues.…”
Section: Resultsmentioning
confidence: 99%
“…We observed that only animals expressing ALG-2(CD) in alg-1(null) background were the only ones showing reduced fitness to a level greater than seen in alg-1(null) animals (Figure 1C , S3A ). As an increased growing temperature creates physiological stress ( 48 , 49 ), we next surveyed the phenotypes of the different mutant animals by maintaining them for at least three generations at 25°C. In this specific condition, while single mutants, alg-1 and alg-2 catalytically dead animals displayed no significant health issues.…”
Section: Resultsmentioning
confidence: 99%
“…INS-39 has recently been reported to be expressed in AFD neurons 89 , but its male pattern suggests a broader expression. To determine the complete expression pattern for INS-39, we generated a nuclear-localized CRISPR/Cas9-engineered reporter allele [ ins-39 ::SL2::GFP::H2B] (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The survival assay was conducted on solid agar plates containing tert-butyl hydroperoxide at a final concentration of 6 mM, following previous protocols 89 , with slight modifications. To prepare the assay plates, tert-butyl hydroperoxide was added to molten agar maintained at 55 °C, and 12 ml of the mixture was poured onto 60 mm NGM agar plates.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations